Safe and Metal-Free Synthesis of 1-Alkenyl Aryl Sulfides and Their Sulfones from Thiiranes and Diaryliodonium Salts - Dong, Jun; Xu, Jiaxi (Synthesis, 2018)
A series of 1-alkenyl aryl sulfides was synthesized from thiiranes and diaryliodonium salts in tetrahydrofuran in the presence of potassium tert-butoxide. The proposed reaction mechanism involves generation of benzynes from the diaryliodonium salts in the presence of the base. Then, nucleophilic attack of the benzynes by thiiranes, followed by hydrogen abstraction and ring opening of the generated thiiranium intermediates, provides the sulfides. These sulfides were further oxidized with performic acid to the corresponding sulfones. The current method provides a metal-free and safe method for the preparation of 1-alkenyl aryl sulfides and their sulfones.
Keywords: benzynes; diaryliodonium salts; sulfides; sulfones; thiiranes; ring opening